2011
DOI: 10.1080/20786204.2011.10874064
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in children and adolescents seen during 2006 at the emergency department of the National District Hospital, Bloemfontein

Abstract: S Afr Fam Pract 2011;53(1):77-82Background: Most children and adolescents recover fully from injuries. However, permanent disabilities may occur. The objective of the study was to investigate the prevalence and profile of injuries in children and adolescents five to 19 years of age seen at the emergency department of the National District Hospital in Bloemfontein.Methods: A retrospective descriptive study was conducted. Demographic and injury-specific information obtained from hospital records of 2006 was ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…present study is in agreement with Pinkett et al and18 Monese et al who reported similar results. However, our study is at variance with Greenes and23 24…”
supporting
confidence: 94%
“…present study is in agreement with Pinkett et al and18 Monese et al who reported similar results. However, our study is at variance with Greenes and23 24…”
supporting
confidence: 94%